Efecto de la ley orgánica para el fortalecimiento de la economía familiar en la rentabilidad de una empresa comercial perteneciente al régimen especial RIMPE emprendedores - Auhing Castro, Keiko Denisse (2024)
This research analyzes the impact of the Organic Law for the Strengthening of Family Economy on the profitability of a commercial company classified under the RIMPE Entrepreneurs Special Regime in the city of Guayaquil. The selected company is dedicated to selling home decor items. The study focuses on evaluating the reforms introduced by the law and their effect on the company's tax obligations and accounting management. A comparative analysis of profitability before and after the law's implementation was conducted, identifying the challenges and benefits arising from its application. The findings show that, while the law offers significant tax advantages, its implementation also presents challenges related to the adaptation of accounting systems and staff training. The conclusions highlight the need for correct interpretation and application of the reforms to maximize their benefits and minimize their negative impact on business profitability.